1993
DOI: 10.1111/j.1440-169x.1993.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Starfish Eggs by Electric Cell Fusion: A New Method of Detect the Cytoplasmic Determinant for Archenteron Formation

Abstract: A method of detecting cytoplasm carrying the determinant for archenteron formation in starfish was established. Animal egg fragments (AEFs) which had been severed from the vegetal halves were fused electrically into pairs with fragments prepared from various regions of immature oocytes. It has been previously shown that the vegetal halves are exclusively endowed with the ability to form the archenteron; AEFs alone develop into so-called permanent blastulae. Eggs thus reconstructed were allowed to develop in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…More recent studies in the starfish showed that a relatively small region of the vegetal hemisphere contained the material necessary for endoderm specification (Kuraishi and Osanai, 1994). If that small vegetal region was removed, an archenteron failed to appear (Kiyomoto and Shirai, 1993). Those studies, and others like them, extending to vertebrates, strongly suggested that information near the vegetal pole was important for activating endomesoderm specification, but the identity of the active principle in the vegetal region remained unknown.…”
Section: Introductionmentioning
confidence: 96%
“…More recent studies in the starfish showed that a relatively small region of the vegetal hemisphere contained the material necessary for endoderm specification (Kuraishi and Osanai, 1994). If that small vegetal region was removed, an archenteron failed to appear (Kiyomoto and Shirai, 1993). Those studies, and others like them, extending to vertebrates, strongly suggested that information near the vegetal pole was important for activating endomesoderm specification, but the identity of the active principle in the vegetal region remained unknown.…”
Section: Introductionmentioning
confidence: 96%
“…As materials for analyzing nucleocytoplasmic relations, starfish eggs are preferable to sea urchin eggs in several respects: (i) the large size of the starfish egg makes the bisection easier; (ii) lack of a rigid hyaline layer facilitates the dissociation of blastomeres; and (iii) the ploidy of embryos can be doubled by blocking the formation of polar bodies (Obata & Nemoto 1984). Moreover, routine procedures for the electric fusion of starfish eggs have been described (Kiyomoto & Shirai 1993; Yoneda 1997), by which we can increase the volume of the cytoplasm of an egg. The last method has never been used in analyzing the timing mechanism operating during cleavage stages; we are the first to use it.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades several methods have been introduced to fuse oocytes of different organisms, for instance with (Vassetzky 1983;Gulyas et al 1984), electrofusion (Kiyomoto and Shirai 1993;Yoneda 1997) or inactivated Sendai virus (Nogue et al 1994). For the questions we addressed here these methods are not suitable because the body size and construction of nematodes with a single-chamber hydroskeleton do not permit removal, manipulation and re-implantation of the small, sensitive oocytes (>50 µm long), as can be done in mouse.…”
Section: Experimental Cell Fusionmentioning
confidence: 98%